A case of platelet transfusion refractoriness occurring after platelet transfusion for tooth extraction in myelodysplastic syndromes patient. Issue 6 (November 2018) - Soma, Tomoya; Asoda, Seiji; Iwasaki, Ryotaro; Miyashita, Hidetaka; Inoue, Mariko; Yamada, Yuka; Uchiyama, Kimio; Nakagawa, Taneaki; Kawana, Hiromasa
Abstract: Myelodysplastic syndrome is an acquired hematopoietic disorder showing symptoms of pre-leukemia and refractory anemia. In the tooth extraction process of such cases, bleeding tendency due to pancytopenia, infection etc., becomes a problem. As such, a cautious approach is required. We have confirmed platelet transfusion refractoriness prior to tooth extraction in a myelodysplastic syndrome patient, and hereby report a case of tooth extraction following human leukocyte antigen (HLA)-compatible concentrated platelet transfusion. The patient was a 55-year-old female who was examined at our department due to a request for the extraction of tooth No. 36. Following consultation at the Hematology Department, platelet transfusion was performed as a pretreatment upon hospitalization. Increased body temperature, chills, shivers, and feelings of discomfort in the pharynx were observed. A close examination was performed due to a lack of increase in platelet count, and revealed platelet transfusion refractoriness caused by anti-HLA antibodies. Therefore, the patient was re-hospitalized and transfused with a platelet concentrate-HLA preparation. One hour later, an increase in platelet count was confirmed and the tooth extraction was performed. There was no evidence of bleeding or infection following extraction, and the prognosis was good.